ANALISIS EFEKTIVITAS PENERAPAN KEBIJAKAN BARU BANK INDONESIA MENGENAI PERUBAHAN BI RATE MENJADI BI-7DAYS REPO RATE TERHADAP PERKEMBANGAN INFLASI DI INDONESIA TAHUN 2011-2020. - Wandi Nofiesti Annisa; Iyan Yani Rita; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine whether changes in Bank Indonesia's policy, namely changing the old benchmark interest rate of the BI Rate to a new benchmark rate, namely the BI 7-Days Repo Rate, which lasts from one month to one week, is more effective in suppressing and controlling inflation. in Indonesia. The data used in this study are quarterly data from 2011 to 2020. The analytical method used is descriptive quantitative and analyzed with the Vector Error Correction Model (VECM) approach using the computer statistical program Eviews version 10. The results of this study indicate that the old benchmark interest rate, namely the BI Rate, is considered ineffective in suppressing and controlling inflation in Indonesia. Meanwhile, Bank Indonesia, which changed its policy and set a new benchmark interest rate, namely the BI 7-Days Repo Rate, is considered effective in suppressing and controlling inflation in Indonesia.Keywords: Effectiveness, BI Rate, BI 7-Days Repo Rate, Inflation